Latin American universities and the third mission : trends, challenges, and policy options - Thorn, Kristian (Policy research working paper, 2006)
"Universities in Latin America are increasingly considered instruments of social and economic development and face rising expectations in regard to supplying relevant skills, undertaking applied research, and engaging in commercial activity. The paper discusses trends and challenges within Latin American universities, as well as policy options available for strengthening their contributions to social and economic development. The so-called third mission of universities is often equated with knowledge transfer narrowly defined as licensing and commercialization of research. The paper adopts a broader approach and explores how the new role of universities affects all aspects of academic practice in Latin America, including advanced education and research. It concludes that policymakers and university managers in Latin America face an important challenge of defining a legal framework, sound management procedures, and notably, incentive systems that stimulate outreach and entrepreneurship among students and staff while recognizing and preserving the distinct roles of universities. "--World Bank web site